Functions of hUpf3a and hUpf3b in nonsense-mediated mRNA decay and translation - Kunz, Joachim B. (Cold Spring Harbor Laboratory Press, 2006)
The exon–junction complex (EJC) components hUpf3a and hUpf3b serve a dual function: They promote nonsense-mediated mRNA decay (NMD), and they also regulate translation efficiency. Whether these two functions are interdependent or independent of each other is unknown. We characterized the function of the hUpf3 proteins in a λN/boxB-based tethering system. Despite the high degree of sequence similarity between hUpf3b and hUpf3a, hUpf3a is much less active than hUpf3b to induce NMD and to stimulate translation. We show that induction of NMD by hUpf3 proteins requires interaction with Y14, Magoh, BTZ, and eIF4AIII. The protein region that mediates this interaction and discriminates between hUpf3a and hUpf3b in NMD function is located in the C-terminal domain and fully contained within a small sequence that is highly conserved in Upf3b but not Upf3a proteins. Stimulation of translation is independent of this interaction and is determined by other regions of the hUpf3 protein, indicating the presence of different downstream pathways of hUpf3 proteins either in NMD or in translation.